Evaluate using suitable identity :48^2

<br>(48)<sup>2</sup> = (50 – 2)<sup>2</sup></br>

<br>Since (a – b)<sup>2</sup> = a<sup>2</sup> – 2ab + b<sup>2</sup></br>

<br>therefore (50 – 2)<sup>2</sup> = (50)<sup>2</sup> – 2 × 50 × 2 + (2)<sup>2</sup></br> 

<br>= 2500 – 200 + 4 = 2504 – 200 = 2304</br>

Was this answer helpful?

 
   

0 (0)

(0)
(0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question